The Relationship Between the Physical Health of Pregnant Women and The Social Economy - Iman Sari, Asri; Zannah, Ai Nur; Yuningsih, Yuningsih (Universitas Islam Jember, 2023)
Midwives provide continuous and plenary midwifery services, focusing on aspects of prevention, promotion based on partnerships and community empowerment together with other health workers to always be ready to serve. Pregnant women need holistic care to meet basic needs, not only biological needs with the 10T examination but also psychological, social, cultural and spiritual examinations with a holistic examination covering the mother's physical, psychological, social and even spiritual condition. . The instrument in this study was a questionnaire consisting of questionnaires on social and economic factors as well as measurements of general maternal data such as weight, height and other routine measurements for pregnant women. After a statistical test was carried out using the Spearman rank correlation, it was found that the p-value was -0.073 with a significant level of 0.566, which means that the variable physical status of pregnant women seen from BMI and socio-economic status of the mother has a fairly strong but not significant relationship in the opposite direction. Not only social and economic factors that affect the welfare of pregnant women. Routine holistic care is needed for pregnant women to monitor quality pregnancies.